1996
DOI: 10.1073/pnas.93.10.4879
|View full text |Cite
|
Sign up to set email alerts
|

4-Oxoretinol, a new natural ligand and transactivator of the retinoic acid receptors.

Abstract: All-trans-retinoic acid (at-RA) induces cell differentiation in a wide variety of cell types, including F9 embryonic teratocarcinoma cells, and can influence axial pattern formation during embryonic development. We now identify a novel retinoid synthetic pathway in differentiating F9 cells that results in the intracellular production of 4-oxoretinol (4-oxo-ROL) from retinol (vitamin A). Approximately 10-15% of the total retinol in the culture is metabolized to 4-hydroxyretinol and 4-oxo-ROL by the at-RA-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 24 publications
5
76
1
Order By: Relevance
“…In addition, variations in the residual levels of retinoic acid may account for the variability of the phenotypic rescue. The present data do not exclude any possible role for 4-oxo-retinol 17,18 .…”
Section: And C)mentioning
confidence: 55%
“…In addition, variations in the residual levels of retinoic acid may account for the variability of the phenotypic rescue. The present data do not exclude any possible role for 4-oxo-retinol 17,18 .…”
Section: And C)mentioning
confidence: 55%
“…The correlation that we observed between RA metabolism and P450RAI expression does not preclude the possibility that other enzymes are involved in the observed RA metabolism. RA-inducible retinol metabolism has been reported in F9 cells (45,46), and because P450RAI does not metabolize retinol in transfected-COS cells (28), a different enzyme may be involved in retinol metabolism. The enzyme responsible for this activity has not been identified, but it may also have the ability to metabolize RA.…”
Section: Resultsmentioning
confidence: 99%
“…By activation of these nuclear receptors retinoic acids can influence the transcription of various retinoid-response genes (De Luca, 1991). In addition to the retinoic acids several other retinoids, such as 13,14-dihydroretinoic acid (Moise et al 2004(Moise et al , 2005, 3,4-didehydroretinoic acids (Allenby et al 1993), 4-oxo-retinol (Achkar et al 1996) and also 4-oxoretinoic acids (Baron et al 2005), have been found to be potent activators of RAR (Fig. 2).…”
Section: Mechanism Of Action Of Retinoidsmentioning
confidence: 99%